2001
DOI: 10.1136/jnnp.70.4.428
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of epilepsy genetics

Abstract: An overemphasis on molecular genetic advances in epilepsy is in danger of missing the major contribution that clinical genetic studies make in predicting the likely benefit of molecular research eVorts. Genetic epidemiology, twin, and family studies suggest that some individual epilepsy genes raise the risk for developing many diVerent types of epilepsy but that specific combinations of these genes determine specific epilepsy phenotypes. Experimental data show how diVerences in drug response can result from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These have helped but not contributed much toward understanding the basic mechanisms of human epileptogenesis. Conversely, epilepsies with predominantly a complex genetic predisposition are common and account for ∼50% of all genetically based epilepsies (8).…”
Section: Some Recent Advances In Genetics Of Human Epilepsiesmentioning
confidence: 99%
“…These have helped but not contributed much toward understanding the basic mechanisms of human epileptogenesis. Conversely, epilepsies with predominantly a complex genetic predisposition are common and account for ∼50% of all genetically based epilepsies (8).…”
Section: Some Recent Advances In Genetics Of Human Epilepsiesmentioning
confidence: 99%
“…In addition, a family history of epilepsy seems to enhance the risk of epilepsy (Bitterncoourt et al, 1999). For epilepsy resulting from parasitic infections, the interaction between parasitic agents, social economic status, genetics and environmental factors determines the magnitude of developing epilepsy (Johnson & Sander, 2001). In general, in subSaharan Africa, the aetiology of epilepsy is multifactorial and may include different agents such as helminths and protozoans.…”
Section: Epidemiology Of Epilepsy and Parasitic Infections In Sub-sahmentioning
confidence: 99%
“…It is has been suggested that endemic infections are the main reason for the increased incidence of epilepsy in developing countries in conjunction with other factors, such as environmental and social factors (e.g. tropical climate, ecological niches, poor sanitation, malnutrition, inadequate health delivery systems) (4, 6, 14).…”
Section: Endemic Infectionsmentioning
confidence: 99%